Posterior Reversible Encephalopathy Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2013)
Investigators at University of Milan, Italy, report a 6-year-old boy who presented with left-sided weakness followed by status epilepticus, left-sided tonic-clonic seizures with secondary generalization, without fever.